Prototype Design of IoT-Based Real-time Monitoring and Security System for University Server Room - Waworundeng, Jacquline; Korompis, Hilkia Heart (Fakultas Ilmu Komputer, Universitas Klabat, 2024)
The server rooms consist of computing devices hosting essential data which is critical for the operation of universities. Ensuring server room environmental stability and security is vital to prevent data loss and service disruptions. This study presents the design of an IoT-based real-time monitoring and security system for university server rooms to help the IT staff monitor the conditions of the server room. The system aims to enhance server room management efficiency while mitigating risks associated with server room issues and unauthorized access. The research is conducted based on a prototyping model which integrates hardware and software. The main focus is on the construction of the prototype device as a monitoring tool to monitor the server room environment based on the sensor parameters. The prototype has sensors to detect temperature, humidity, smoke, flame, dust, and motion as well as a real-time camera to provide continuous environmental monitoring and intrusion detection. On the software side, the functional design is presented using Unified Modeling Language. Data collected by the sensors are transmitted to IoT platforms for further analysis and visualization, enabling remote monitoring and instant notifications. The research result is a hardware prototype designed with an IoT system that is potentially used to monitor the server room environment.